O impacto dos grupos de referência, da distorção seletiva e da distribuição do tempo discricionário no abandono do consumidor de atividade física em academias - Munaier, Christian Gomes e Souza (2019)
Sedentarism kills. Physical inactivity is responsible for 75.8% of deaths in Brazil. In 2015, Chronic Noncommunicable Diseases (NCDs) accounted for three out of four deaths in the country. Physical inactivity, poor diet, and obesity, as well as smoking, are at the core of the causes of NCDs. More than 54% of the population of the Brazilian capitals is overweight. Young people and adults 15 years of age and older who did not practice any kind of sport or physical activity in Brazil totaled 100.5 million in 2015. Among the reasons for inactivity, research by IBGE points out: “lack of time”, “do not like or do not want to”, “financial problems”, “lack of accessible or nearby sports facilities”, “lack of company to practice the sport”, and others. In Brazil, if sedentary lifestyle were reduced to half of what we see today, there would be a savings of US $ 1.14 billion in health resources. Part of the solution lies in physical activity, and understanding the reasons for the “abandonment” of regular physical exercise practiced in gyms is the subject of this thesis. From a quantitative point of view, we seek to know a) the impact of the influence of the Reference Groups on the decision-making of the former practitioner for not practicing physical activity in the gym; b) the impact of Selective Distortion on the former practitioner's behavior in relation to the importance of physical activity practice in academia; and c) what importance the former practitioner attaches to the distribution of his free time for physical activity in the gym. Inference was also made about the moderating variable “length of stay in a gym” to assess abandonment behavior. A survey scale was proposed and applied to 400 respondents, 200 practitioners, and 200 former academics. From its results, a multivariate analysis was performed to observe or reject the hypotheses contained in the Conceptual Model elaborated by the author, noting that 1) the more sensitive the individual is to their Reference Groups, the greater their chances of leaving the academy; 2) that the former practitioner does not see the gym as a priority for the pursuit of a healthier and longer life; and 3) that the former practitioner prefers to give a more playful fate to his discretionary time rather than attend a gym.